PENDIDIKAN AGAMA ISLAM UNTUK SISWA DIFABEL: KAJIAN TEORITIS DAN PRAKTIS TENTANG PENDEKATAN INKLUSIF - Yanti, Ulfa (Tarbiyah bil Qalam : Jurnal Pendidikan Agama dan Sains, 2024)
Islamic Religious Education (PAI) has a central role in shaping the character and Islamic values of students, including students with disabilities. This study aims to examine the theoretical and practical approaches in the implementation of inclusive PAI for students with disabilities. The research method used is a literature review, by analyzing books, scientific journals, and the latest education policies. The results showed that the success of inclusive PAI requires curriculum adaptation, teacher training, and provision of facilities that support the needs of students with disabilities. Recommendations include strengthening teachers' competencies through training, developing a flexible curriculum, and implementing collaborative learning methods. This study contributes to the development of religious education that is equitable and relevant to the needs of all students.